THE ROLE OF SOCIAL MEDIA IN BUILDING A BRAND IMAGE TO MAINTAIN A CORPORATE IMAGE ON TPA (THIRD PARTY ASSITANCE) COMPANIES - Baskoro, Arga (Fakultas Komunikasi, Sastra, dan Bahasa, 2021)
The increasing number of social media users has presented new media for public relations communication. This is then used by companies to maximize social media to provide information about products or services. This study aims to determine the role of social media in building brand image and its role in maintaining corporate image. The concept which uses in this study are the Social Media network, MPR, Cyber PR, Brand Image, and Corporate Image. The research objects are social media of TPA (Third Party Assistance) Companies such as AAI Indonesia, Fullerton, Admedika and Owlexa. This study uses post positivist paradigm, a qualitative approach and is descriptive in nature. In this study it was found that social media is not instrumental tools in building their brand image and also not play a role in maintaining the corporate image.